Talent Management and Financial Performance: Does Organization Learning Mediate That Relationship? - Tarigan, Josua; Ferdian, Gabriele Nia; Hatane, Saarce Elsye; Dharmayanti, Diah (Department of Management, Faculty of Economics and Business, Brawijaya University, 2018)
This research has a purpose to identify the impact of the talent management through organization learning towards the financial performance of the listed consumer goods sector in Indonesia. Indonesia costumer goods sector has faced significant growth during the recent year, the companies are enforced to establish competitive strategy to maintain their position in the market. Talent management should be paid attention more since it helps the company to attract, acquire, and retain the best employees that may help maintaining their position in the market as well as enhancing the performance. Based on the hypothesis test, it is true that talent management influences organization learning and financial performance. The companies such as PT HM Sampoerna Tbk and PT Unilever Tbk who obtain high score in the talent management variable most likely to be followed by high score in the organization learning as well. The results also reveal that some companies still need to improve the attraction activities and system to capture learning which are the first indicator of talent management and forth indicator of organization learning. In addition, it was found that organization learning as a mediator can strengthen the relationship between talent management and financial performance.